Sustainable Tour Operators: The Case of Seascape Kayak Tours Inc. in Costa Rica - Wood's, Greg (2018)
Seascape Kayak Tours Inc. is a small adventure tour company started by a Canadian entrepreneur. The company offers kayaking tours in Deer Island, New Brunswick, Canada and in Playa Tambor, Costa Rica. Data for the case was collected from public sources, interview with the owner, as well as from ethnographic observation and parti cipation. The case research focuses on the issue of sustainable tour operators and uses Seascape to highlight the importance of sustainable beliefs and philosophy